Social Housing and Territorial Stigma: Between Social Representations and the Lived Experiences of Residents: https://doi.org/10.60543/ts_iss.vi10.11691 ("Temas Sociais" Journal, 2026)
Social housing is a key instrument for ensuring the right to adequate housing. However, social housing contexts may be characterised by negative social representations and experiences of stigmatisation and discrimination that affect community cohesion. This study aimed to explore residents' perceptions of the impact of social housing on their quality of life, community relationships, and in how stigma associated with their residential area influences their lived experiences and social integration. A qualitative methodology was adopted, using semi-structured interviews with ten residents of social housing neighborhoods in northern Portugal. The findings indicate that, despite improvements in housing conditions and well-being, negative social representations of social housing persist. Although most participants did not report experiencing direct discrimination, they acknowledged the existence of stereotypes that shape public perceptions of these communities. The study highlights the importance of social work in promoting social inclusion, community participation, and stronger community cohesion.
Keywords: Social Housing; Stigma; Discrimination; Community